Fabrication of a 2-DOF electromagnetic energy harvester with in-phase vibrational bandwidth broadening. (12th August 2016) - Chen, Shih-Jui; Wu, Jia-Yin
Abstract: A vibration structure with two-degrees-of-freedom is proposed to increase the usable bandwidth of a micromachined electromagnetic energy harvester. Compared with the structure of a pure cantilever harvester, the proposed structure is formed by integrating a spiral diaphragm into a U-shaped cantilever diaphragm. By performing finite element analysis, the resonance frequencies of the two diaphragms are designed with a slight shift, both lower than 300 Hz. In addition, to achieve output bandwidth broadening, electroplated copper coils on the spiral and the U-shaped cantilever are coupled and the connection sequences of the coupled coils are arranged such that single- or duo-mode tuning of the energy harvester can be realized. The harvester delivers powers of 22.1 and 21.5 nW at two resonance frequencies of 211 and 274 Hz, respectively, in the duo-mode operation. The proposed spiral–cantilever coupled energy harvester has lower resonance frequencies and broader bandwidth than a pure cantilever-type harvester of equal area, and can therefore harvest more energy from the environment.